Analisis Atas Keabsahan Perkawinan Beda Agama - Hamdan Nasution (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
Marital status of different religions in the legal system in Indonesia is illegitimate. Marriage Law Number 1 of 1974 in Article 2 paragraph 1 reveals that marriage is legal if it is carried out according to the law of each religion and belief. It means that marriage can only take place if the parties (future husband and wife) follow the same religion. From the formulation of Article 2 paragraph 1, there are no marriages outside their respective laws and beliefs. Interfaith marriages are held abroad. Keywords: Analysis, Legitimacy, Interfaith Marriage